PRODUCTION OF MAGNESIUM FROM DOLOMITE BY PIDGEON PROCESS USING VERTICAL RETORT - Yasin Siregar, Mhd.
With the rapid development of applications for magnesium-based alloys, the demand for primary magnesium is increasing drastically worldwide. Magnesium is a light metal among other structural metals. One of its main purposes in automotive applications is to reduce fuel consumption. Magnesium can be produced by electrolysis of fused magnesium chloride or high temperature reduction of the magnesium oxide. Magnesium metal is generally produced from calcined dolomite by a silicothermic process in a vacuum. The Pidgeon process is the most widely used process for producing magnesium, but it has its own problems such as high energy consumption and environmental pollution. In this research, the reduction of calcined dolomite with ferrosilicon and aluminum as a reducing agent has been studied with the addition CaF2 and B2O3 as additives. A series of calcined dolomite reduction experiments were carried out in a vertical retort mounted in a vertical furnace which was vacuumed using a vacuum pump to a pressure below 10 Pa. The furnace temperature was heated with a rate of 10 oC per minute until it reached a temperatur of 1200 oC. After holding 8 hours at 1200 oC, the furnace temperatur was lowered with a cooling rate of 10 oC per minute to room temperature. Experiments were carried out by varying the reducing agent aluminum and ferrosilicon, and variations in the composition of additives CaF2 and B2O3 starting from 3% B2O3, 1.5% CaF2 - 1.5% B2O3, 3% CaF2 - 3% B2O3 and 3 % CaF2. Experimental variations in the composition of additives were carried out using a ferrosilicone reductant with additions excess to stoichiometric requirements to reduce dolomite calcine samples. The resulting magnesium metal was analyzed by X-Ray Diffraction (XRD) and Scanning Electron Microscope - Energy Dispersive X-Ray Spectroscopy (SEM-EDS). The residues produced were analyzed by XRD, XRF, and SEM-EDS. The experimental results obtained in this study include data on changes in sample weight, compounds in the sample using XRD, composition of elements in the sample using XRF, chemical composition of the phases in the sample from spot analysis using SEM-EDS, and average chemical composition, and average chemical composition from area analysis using SEM-EDS. Increasing the calcination temperature decreases the percentage of sample weight loss in the final mass of the residue. Reduction experiment of sample with calcination temperature 900?C